A comparison of computational and experimental results of Wells turbine performance for wave energy conversion - Taha, Z.; Sugiyono, -; Sawada, T. (Elsevier, 2010)
This paper presents an investigation on the performance of a Wells turbine for wave energy conversion using computational fluid dynamics (CFD). The investigation was performed on numerical models of a NACA0020 blade profile with various uniform tip clearances under steady flow conditions. The main objective of this investigation is to compare computational and experimental results, particularly for the cases of tip clearance to chord length ratios of 0.0056 and 0.0111. Further, the effect of tip clearance on the turbine performance can also be observed. It was shown that there was good agreement between the computational and experimental results for both cases of tip clearance to chord length ratio in terms of torque and power coefficients, and efficiency. It was also shown clearly that the turbine performance is influenced significantly by tip clearance. The tip leakage flow constituted an important factor which determined the turbine performance. An investigation on the flow-field around the turbine blade was performed to explain the phenomena. (C) 2010 Elsevier Ltd. All rights reserved.